Can official development assistance promote financial development in developing countries? - PARK, Yumi (KDI School, 2015)
The role of foreign aid on economic development has been an inconclusive and tedious debate for decades. In the meantime, most of studies on financial development and economic growth conclude that financial development significantly and positively affects economic development. Only few studies, however, shed light on foreign aid as a determinant of financial development. Based on the findings of positive role financial development on economic growth, this paper explores the aspect of official development assistance as a determinant of financial development that can lead economic development in developing countries. The empirical result shows that official development assistance significant and negative on both financial depth and breadth than other foreign capital inflows, such as remittances and foreign direct investment in developing countries. The results come up with future policy implications on delivery aid and reporting system of official development assistance.
Thesis(Master) --KDI School:Master of Development Policy,2015